Verification of disease management technology on lentil against Stemphylium blight at farmer’s field in Nepal - Subedi, Subash; Neupane, Sarswati (Journal of Agriculture and Natural Resources, 2018)
Technologies generated from lentil (Lens culinaris Medik) stemphylium blight (Stemphylium botryosum Walr) management experiments were verified at farmers field of 5 districts viz., Chitawan, Rautahat, Dang, Parsa and Banke during two winter seasons of 2013-2014 and 2014- 2015. The experiment was laid out in randomized complete block design with factorial arrangement of treatments and replicated 4 times. The plot size was 340 m2 (1 Kattha) with 25 cm row to row spacing. There were altogether 3 factors of the experiment i.e. year (2013-2014 and 2014-2015), location (5 districts) and package of practice (improved and farmers practice). The higher crop yield (1142.50 kg/ha) with lower disease index (34.95%) and higher benefit cost ratio of 2.42 were recorded in the farmers field of Banke district following seed rate (30 kg/ha), 8 hour primed improved variety (Black lentil), fertilizer doze of (20:40:20 NPK kg/ha+ 1 kg/ha B basal doze) and subsequent 3 sprays of Dithane M-45 @ 2.5 g/l of water at 10 days interval.